Estudio comparativo de estructuras de educación y atención a la infancia en siete países: Australia, Bélgica, Brasil, Canadá, Cuba, Francia y Perú - Jessica Vargas D'Uniam (Pontificia Universidad Católica del Perú, 2011)
A comparative study of educational structures that receive children less than six years old in seven countries: Australia, Brazil, Belgium, Canada, Cuba, France and Peru This investigation comprises a comparative study of educational structures that receive children under six years old in seven countries: Australia, Brazil, Belgium, Canada, Cuba, France and Peru. The goal of this research is identify and analyze the educational structures that receive children under six years old. This analysis displays the mechanisms that they develop as an answer to their characteristics and particular needs. The analysis of the results conclude that the organization of the educational structures addressed to service little children, depends on various factors (i.e. social, economic, cultural, geographical, etcétera), and can be configured in a different way than the services and programs of education, ultimately responding to the characteristics and needs of children, their families and their community. Keywords: Early-childhood education, educational pre-school structures, preschool institutions.